How International Health System Austerity Responses to the 2008 Financial Crisis Impacted Health System and Workforce Resilience – A Realist Review - Padraic Fleming; Louise Caffrey; Sara Van Belle; Sarah Barry; Sara Burke; Jacki Conway; Rikke Siersbaek; David Mockler; Steve Thomas (International Journal of Health Policy and Management, 2023)
Background  The Great Recession, following the 2008 financial crisis, led many governments to adopt programmes of austerity. This had a lasting impact on health system functionality, resources, staff (numbers, motivation and morale) and patient outcomes. This study aimed to understand how health system resilience was impacted and how this affects readiness for subsequent shocks.Methods  A realist review identified legacies associated with austerity (proximal outcomes) and how these impact the distal outcome of health system resilience. EMBASE, CINAHL, MEDLINE, EconLit and Web of Science were searched (2007–May 2021), resulting in 1081 articles. Further theory-driven searches resulted in an additional 60 studies. Descriptive, inductive, deductive and retroductive realist analysis (utilising excel and Nvivo) aided the development of context-mechanism-outcome configurations (CMOCs), alongside stakeholder engagement to confirm or refute emerging results. Causal pathways, and the interplay between context and mechanisms that led to proximal and distal outcomes, were revealed. The refined CMOCs and policy recommendations focused primarily on workforce resilience.Results  Five CMOCs demonstrated how austerity-driven policy decisions can impact health systems when driven by the priorities of external agents. This created a real or perceived shift away from the values and interests of health professionals, a distrust in decision-making processes and resistance to change. Their values were at odds with the realities of implementing such policy decisions within sustained restrictive working conditions (rationing of staff, consumables, treatment options). A diminished view of the profession and an inability to provide high-quality, equitable, and needs-led care, alongside stagnant or degraded working conditions, led to moral distress. This can forge legacies that may adversely impact resilience when faced with future shocks.Conclusion  This review reveals the importance of transparent, open communication, in addition to co-produced policies in order to avoid scenarios that can be detrimental to workforce and health system resilience.